PS-110 Extent and diversity of day-to-day clinical pharmacists' interventions in hospitals. (24th March 2015) - Langebrake, C; Ihbe-Heffinger, A; Leichenberg, K; Kaden, S; Kunkel, M; Lueb, M; Hilgarth, H; Hohmann, C
Abstract : Background: Clinical pharmacy services (CPS) are known to improve medication safety and patients' clinical outcome. However, in the majority of the European countries their implementation is low and there are no nationwide reports about the nature of clinical pharmacists' interventions (CPIs) in European hospitals outside the UK. Purpose: To evaluate both the extent and diversity of data about national hospital CPIs nationwide. Material and methods: Datasets from ADKA-DokuPIK, an anonymous and voluntary German database for the documentation of hospital CPIs with >500 registered users, which were entered between 01/2009 and 12/2012, were analysed descriptively. Results: In total, 27, 610 CPIs were recorded, with an upward trend over the years. The vast majority of CPIs were performed by ward-based pharmacists (82.5%), mainly on surgical wards (37.8%), followed by anaesthesiology/ICU/IMC (16.8%) and internal medicine (10.8%). More than half of the patients were >65 years. The main reasons for CPIs were inappropriate use of drugs (including over- and underuse, inappropriate choice of drug and/or formulation, generic or therapeutic substitution) (23.2%) and wrong dose or administration interval (22.2%) resulting in the most frequently taken actions of change of dose, change of drug and drug stopped/paused. The therapeutic subgroup with most interventions was antibacterials for systemic use (13.9%) followed by antithrombotic agents (6.9%), analgesics (6.7%), drugs for acid-related disorders (5.9%) and agents acting on the renin-angiotensin system (5.4%). Altogether, the acceptance rate of the CPIs was 85.5%. Underlying medication errors were predominantly classified as "error, no harm", while 4.1% were classified as "error, harm or death" according to NCC-MERP. Conclusion: For the first time we demonstrated clinical pharmacists' involvement nationwide in daily clinical practice in a non-UK European country. Although the overall rate of CPIs cannot be calculated due to the anonymous and voluntary data collection, the results might help to further strengthen the demand for CPS in Germany. References and/or acknowledgements: Thanks to all ADKA-DokuPIK users. No conflict of interest.